Predicting safety compliance and behaviour: An extended theory of planned behaviour - Lim, Chun Aik; Chai, Changsaar; Lee, Chia Kuang (Taylor's University, 2024)
The construction industry is considered one of the most dangerous industries due to the complexity and uncertainty associated with construction projects. Safety compliance in the construction industry has attracted significant attention from researchers and practitioners in recent years. Safety compliance is important for minimising accidents in the construction industry. To uphold workplace safety at a construction site, individuals need to actively practise specific and essential behaviours documented through safety compliance measures. Although there is literature on safety compliance in the construction industry, previous studies have overlooked the examination of safety compliance utilisation through the theory of planned behaviour (TPB). The exploration of belief in safety compliance in the construction industry is limited. This research proposes a TPB model to predict the safety compliance intentions of construction workers by investigating salient beliefs, encompassing attitudinal, normative, and control beliefs. Data was collected through an online questionnaire with open-ended questions, which was administered to experts engaged in construction projects in Malaysia. A total of 15 respondents participated in this study and shared their salient beliefs regarding the intention of safety compliance. The beliefs collected from the online survey underwent conceptual content analysis and were categorised into six stable sets of theoretical constructs. Attitudinal Beliefs were decomposed into Perceived Relative Advantages, Normative Beliefs were decomposed into Facilitating Conditions, and Control Beliefs were decomposed into project management teams, local workers, foreign workers, and sub-contractors. A revised conceptual TPB model was formulated to predict safety compliance intention and actual compliance behaviour in the construction industry based on the developed theoretical constructs.